The use of visual media when teaching the skill of writing to autistic students - Faruga, Martyna; Polok, Krzysztof; Przybysz-Zaremba, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2023)
It is believed (Zaorska & Trajdowska, 2013) that autistic students are usually visual learners. It seems that the use of visual media and visually based teaching methods may be beneficial for such students. The aim of the present research was to discover whether visual media can be useful while teaching the skill of writing to autistic students. Furthermore, attempts were made to find out the difference between visually based approaches and non-specific ones when it comes to teaching autistic students. As far as inclusive education in Poland is concerned, the research aimed at showing its efficiency regarding the students with autism. In this paper, we would like to present the findings of our research because we believe that they may be useful for teachers who work with autistic students.